Implementation of Religious Education in Shaping Students' Religious Character: A Case Study at MTs-SA Miftahul Huda 606 Kalianda - M Dzikri Zaini Qolbi; Ihsan Mustofa; Jaenullah Jaenullah (Assyfa Journal of Islamic Studies, 2025)
This study aims to analyze the implementation of religious education in shaping students' religious character and preventing juvenile delinquency at MTs-SA Miftahul Huda 606 Kalianda. A qualitative case study approach was employed. Data were collected through in-depth interviews, participant observation, documentation, and questionnaires. The findings reveal that the objectives of religious education align with Islamic education goals: nurturing faithful, pious, and morally upright individuals. The implementation process includes daily activities (Dhuha prayer, Qur'anic recitation, tahfidz, congregational Dhuhur/Asr prayers), weekly (Friday charity), monthly (moral guidance), and annual (Islamic holiday commemorations). Supporting factors include the principal's commitment, adequate worship facilities, and student awareness. Inhibiting factors include a lack of Qur'anic experts, external environmental influences, and weak rule enforcement. Outcomes include improved worship discipline, strengthened Qur'anic literacy, positive behavioral changes, and school-parent synergy. This study contributes to developing character education through religious activities in madrasahs.